010: POLICY SIMULATION OF THE AQUINO HEALTH AGENDA IN THE PHILIPPINES. (24th August 2015) - Belandres, Rachel Lynn Y
Abstract : Background: Health is an important aspect of human development. However, not everyone, especially the poor, has access to health care services, which is the case in the Philippines. Because of this, the Aquino Health Agenda was developed to address the problem on accessing health care services in the Philippines. Objectives: This study aims to determine if the Aquino Health Agenda policies are really pro-poor and cost effective. Methods: The Aquino Health Agenda policies were tested in terms of equity and efficiency using Benefit Incidence Analysis and Cost Effectiveness Analysis respectively. The policies that were simulated in this study are upgrading health facilities under the Health Facilities Enhancement Program and expanding health insurance coverage under the National Health Insurance Program. In addition, the policy simulation only covered the following Philippine regions: Autonomous Region of Muslim Mindanao, Eastern Visayas, and Bicol Region. Result: The results revealed that when it comes to equity, expanding health insurance coverage is more pro-poor than upgrading of health facilities in ARMM, Eastern Visayas, and Bicol Region. On the other hand, when it comes to efficiency or cost-effectiveness, expanding health insurance coverage is more cost effective in Eastern Visayas, while upgrading of health facilities is more cost effective in ARMM and Bicol Region. Conclusion: Deaspite the given results, it is still highly recommended that both policy options should be implemented, since they complement each other. However, in implementing both policies, the government should take note the specific circumstances of each region, so that they can truly determine what policy they should give more bearing in each of the regions.